Hubungan Antara Jalan Kaki Dengan Vo2 Maksimal Pada Siswi SMA Negeri 1 Ngemplak Boyolali - Taufik, Rizki; , Dwi Rosella K, S.Fis.,Ftr.,M.Fis; , Agus Widodo, S.Fis.,Ftr., M.Fis (2015)
Background: Walking is a kinds of physical excercise done by our feet followed by other parts of our body, such as hands dynamically. This exercise capable to increase our fitness and foot strenght. One of the way to measure someone fitness is by the maximum VO2. Maximum VO2 is a number of oxygen inhale by our body per menit divided by our body mass index. Objective: This research was conducted to find out the relationship of walking exercise toward maximum VO2 of female students at SMA. Research Methodology: This research done by doing observation with Cross Sectional approach to find out the relationship of walking excercise toward the maximum VO2. The Population of this research were the female students of SMA Negeri 1 Ngemplak Boyolali. The total sample taken were 81 students who complete the criteria of inklusi and eksklusi. The measurement of maximum VO2 respondents was done by using Cooper test, while the analysis of this research done by Chi square test analysis. Results: The result done by chi square test gained p = 0.000 which means p <0.05 is denied dan Ha Ho is accepted. Conclusion: There is a significant relationship of walking exercise toward the VO2 max.